Impact of social capital on entrepreneurial intention of polytechnic students: The mediating role of innovativeness - Bhunia, Anish Kumar; Shome, Mihir Kumar (International Journal of Innovative Research and Scientific Studies, 2023)
Entrepreneurship is seen as a crucial component of any nation’s economic progress. The most significant predictor of entrepreneurship is thought to be the entrepreneurial intention. Therefore, it is crucial to understand the variables that shape entrepreneurial intent. The purpose of this study is to investigate how social capital and innovativeness, two significant predictors of entrepreneurial intention, interact to determine the entrepreneurial intention of polytechnic students from the Indian state of Arunachal Pradesh. A questionnaire based on a 5-point Likert scale was completed by 261 polytechnic students (214 male,47 female) from six polytechnic (5 Govt,1 Private) colleges across Arunachal Pradesh. The structure model was examined using structural equation modelling (SEM) analysis in SPSS AMOS (Analysis of Moment Structure), and bootstrap confidence intervals were computed to test the mediating role. The findings showed that both social capital and innovativeness have a significant positive impact on entrepreneurial intention, and innovativeness partially mediates the association between social capital and entrepreneurial intention. Our study’s findings have significant ramifications for vocational educators because they show that emphasizing the importance of social capital and innovativeness might increase polytechnic students’ likelihood to become entrepreneurs.